EPCT-12. NATIONAL MULTICENTERED RETROSPECTIVE REVIEW OF DEMOGRAPHIC, TUMOUR AND INTRAOPERATIVE FEATURES ASSOCIATED WITH THE DEVELOPMENT OF CEREBELLAR MUTISM AFTER PEDIATRIC POSTERIOR FOSSA TUMOUR RESECTION. (1st June 2021) - Kameda-Smith, Michelle; Elliott, Cameron; Moore, Hannna; Sader, Nicholas; Tso, Michael; Alsuwaihel, Mosaab; Dakson, Ayoub; Ajani, Olufemi; Yarascavitch, Blake; Fleming, Adam; Mehta, Vivek; Farrokhyar, Forough; et al.
Abstract: Background: Cerebellar mutism (CM) is a condition characterized by a significant lack or loss of speech in children following posterior fossa (PF) surgery. The biological origin of CM remains largely unclear and remains the subject of ongoing debate. Despite multidisciplinary rehabilitative interventions, the outcome is less favorable than initially described. Given the treatment refractory nature of CM, central to its management is prevention. Methods: A national multi-centered retrospective review of all the children undergoing posterior fossa resection at 4 Canadian academic pediatric institutions was undertaken. Patient, tumour, surgical features suggested to be associated with the post-operative development of CM were reviewed to identify pre-operative and intra-operative factors that may predict post-operative CM occurrence. Results: 258 pediatric patients were identified after posterior fossa lesion resection. Mean age at surgery was 6.74 years (SD 4.60) and 42.2% were female. Frozen section was available in 90.3% of cases. The majority of final tumour histology was medulloblastoma (35.7%), pilocytic astrocytoma (32.6%), ependymoma (17.1%) and exophytic glioma (1.2%). Intra-operative impression of adherence to the floor of the 4th ventricle was negative in 47.7%, positive in 36.8% of cases. The extent of resection assessed intraoperatively as gross total resection was 69.8% of cases. Intra-operative abrupt changes in blood pressure and/or heart rate was identified in 19.4% and 17.8% of cases. CM was experienced in 19.5% of patients (N=50), with the majority of cases identified by post-operative day 7. The clinical resolution of CM as mainly assessed by a neurosurgeon (86%) and was complete, significantly resolved, slight improvement, no improvement or deterioration in 56.0%, 8.0%, 20.0%, 14.0%, 2.0% respectively. Conclusion: As a devastating surgical complication, identifying and understanding the biological origin of CM is the first step to complication avoidance. Maximal safe resection irrespective of intra-operative pathology remains the goal to avoid the devastating complication of CM.